AN–INVESTMENT–RECOVERY–FIRST CONCEPT OF TAXABLE PROFIT. - Carson, A. B. (The Accounting Review, 1951)
Abstract From a tax standpoint, the concept of business income as it exists as a part of the "generally accepted" principles of accounting has some notable weaknesses. The defects are associated primarily with the entity concept, the going concern postulate, and the period convention. To a lesser extent, there are faults connected with the manner in which the realization concept, the "rule of conservatism," and the "maintenance of dollar capital principle" are applied. Most of these deficiencies might be absent or minimal if taxable profit was conceived as an individual matter and considered to arise only after there had been a recovery of the money (or equivalent) that an individual had invested in a profit seeking venture of any sort. The manner of calculating profit, unrecovered investment, or loss would depend, in part, upon the type or nature of the investment. The concept embraces the idea that the tax on profits arising after a short recovery period should be larger than the levy on profits realized after an extended period of investment recovery. There is reason to suggest that a number of desirable consequences might attend the use of such a method of measuring profit for tax purposes. There might be greater equity in taxation in several respects, less risk to investors, and resulting stimulation to the national economy. The danger of inequity in certain other cases, and the possibility that the use of such a method might tend to impede the movement of capital funds are the major negative potentials. In spite of these defects, it is contended that the nation would benefit if means could be found to effect a transition to an investment-recovery-first basis of measuring profit for tax purposes. At the least, the concept might have value as a standard or viewpoint to use in the analysis of the prevailing tax requirements, and in the evaluation of proposed reforms in the tax system.